Association between frailty and pain in older people at high risk of future hospitalization - Dong, Huan-Ji; Yang, Joakim; Johansson, Maria M.; Peolsson, Anneli; Barbero, Marco; Nord, Magnus (Frontiers in Pain Research, 2025)
BackgroundPrevious studies have demonstrated an independent association between pain and frailty, but knowledge about this association with different pain characteristics is limited.ObjectiveThis study was embedded in a prospective, pragmatic, matched-control multicenter trial at 19 primary care practices in south-eastern Sweden (ClinicalTrials.gov 170608, ID: NCT03180606), aiming to investigate the association between frailty and pain characteristics among older people (75+) at high risk of hospitalization.MethodsHigh risk of hospitalization was identified using case-finding algorithm including 32 diagnostic codes of morbidities and healthcare use. Frailty was assessed by a nurse-physician team using Clinical Frailty Scale (N = 389). Data on pain aspects, physical and ADL functioning were collected in the self-reported questionnaires.ResultsOne in three (n = 133, 34%) was classified as frail. About 36% (n = 142) reported frequent pain (from several times per week to constantly). Slightly over 40% reported pain lasting longer than 3 months (n = 163, 41.9%) and/or having regional or widespread pain (n = 165, 42.4%). In comparison to non-frail peers, frail participants reported higher pain intensity, more ADL-dependency, less physical activity, and more anxiety/depression (p < 0.01). In logistic regression analysis, pain frequency [Odds Ratio (OR) 1.8, 95% confidence interval (CI): 1.2–2.8] was associated with frailty. However, the models with ADL-staircase score (OR: 1.4, 95% CI: 1.2–1.6) had a higher explanatory power (Nagelkerke R2: 0.39) in predicting frailty than those without this aspect (R2: 0.10 and 0.13).ConclusionIn older people at high risk of hospitalization, pain frequency seemed to be related to frailty, whilst ADL dependency demonstrated a stronger association.